Achievement Goal Orientations and Self–Regulated Learning Strategies of Adult and Traditional Learners. Issue 4 (September 2018) - Lin, Xi; Wang, Chih–hsuan
Previous studies indicated there was a difference in goal orientations and learning strategies between adult and traditional learners. However, limited studies investigated the relationship between achievement goal orientations (AGO) and self–regulated learning (SRL) between adult and traditional learners. Hence, the current study examined the different levels in AGO and SRL between adult and traditional learners, and the relationship between student status, AGO, and SRL. A total number of 469 students participated in the study, including 228 traditional learners and 240 adult learners. Results indicated that adult learners had higher levels of mastery–approach goal orientation, while traditional students had higher levels of performance–avoidance goal orientation. Additionally, mastery approach goal orientation is usually positively linked with both adult and traditional learners' self–regulated learning strategies, whereas performance avoidance goal orientation is negatively linked with metacognitive self–regulation and effort regulation strategies.